The implementation of mobile libraries (m-libraries) in Open University Malaysia - Shahril Effendi Ibrahim (2012)
This paper highlights the implementation of mobile libraries (m-libraries) initiative at Open University Malaysia (OUM). Established to expand its reach to existing user base and increase its appeal to segments that were previously unreachable, this initiative will support the concept of ubiquitous learning among OUM Learners. The usage of m-libraries among OUM community also will be discussed. Type of information retrieved when using m-libraries will be elaborated. The role of Quick Reading Codes (QR-Codes) in m-libraries environment and findings on usability test on the implementation of OUM m-libraries will be presented. Finally, the future of m-libraries will be briefly discussed.